2023
DOI: 10.1542/peds.2022-059654
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Adverse Outcomes Associated With Teen Dating Violence: A Systematic Review

Abstract: CONTEXT: Evidence suggests that teen dating violence (TDV) is associated with long-term adverse outcomes, but these associations have not been systematically assessed. OBJECTIVES: To conduct a systematic review of the longitudinal associations between TDV and negative outcomes, including mental and physical health, reoccurrence of violence in intimate relationships, and high-risk behaviors (substance use and sexual behaviors)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…For example, they may directly experience parent-child violence or dating violence, or they may be exposed to physical violence between their parents (David-Ferdon et al, 2021;Finkelhor et al, 2015;McDonald et al, 2006;Wincentak et al, 2017). Such experiences increase the risk for adolescent mental health symptoms (traumatic stress, internalizing, and externalizing) and delinquent acts (Gershoff, 2013;Piolanti et al, 2023;Vu et al, 2016). Moreover, exposure to multiple types of interpersonal violence, as compared to a single type, increases the risk for mental health symptoms and delinquent acts even further (e.g., Cheung & Huang, 2023;Gómez, 2011;Jouriles et al, 2012).…”
Section: Abstract Racial Discrimination Exposure To Violence Polyvict...mentioning
confidence: 99%
“…For example, they may directly experience parent-child violence or dating violence, or they may be exposed to physical violence between their parents (David-Ferdon et al, 2021;Finkelhor et al, 2015;McDonald et al, 2006;Wincentak et al, 2017). Such experiences increase the risk for adolescent mental health symptoms (traumatic stress, internalizing, and externalizing) and delinquent acts (Gershoff, 2013;Piolanti et al, 2023;Vu et al, 2016). Moreover, exposure to multiple types of interpersonal violence, as compared to a single type, increases the risk for mental health symptoms and delinquent acts even further (e.g., Cheung & Huang, 2023;Gómez, 2011;Jouriles et al, 2012).…”
Section: Abstract Racial Discrimination Exposure To Violence Polyvict...mentioning
confidence: 99%
“…On the other hand, findings indicate that undergoing dating abuse during adolescence contributes to subsequent experiences of being victimised or perpetrating abuse by a romantic partner later [20,21,24,27]. This underscores the importance of identifying and addressing these violent behaviours from their earliest stages.…”
Section: Introductionmentioning
confidence: 97%
“…In general, studies indicate that young people dating abuse, both victimisation and perpetration, is associated with a range of negative short-and long-term health outcomes [19]. Within the mental and psychological sphere, it has been found that both victims and perpetrators show symptoms of depression and increased suicidal ideation and attempts across time, as well as post-traumatic stress disorder [20,21]. Mental disorders play a dual role, as both risk factors for and outcomes of DV [22].…”
Section: Introductionmentioning
confidence: 99%
“…According to data from the Centers for Disease Control and Prevention (CDC) in the US, TDV is a widespread issue among adolescents, with 8.2% of high school students reporting physical and sexual violence in their romantic relationships ( Basile et al, 2020 ). TDV may represent a risk factor for experiencing violence in adulthood ( Piolanti et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%